The Correlation between Knowledge and Compliance with Personal Protective Equipment (PPE) Use in Construction Workers at EMC Alam Sutera Hospital, South Tangerang City - Melda Siahaan; Sartika, Imas; Saputra, Rangga; Oliber A. Arde, Bernardo (Universitas Nahdlatul Ulama Surabaya, 2023)
Construction work has a high-risk workplace. Construction workers are often faced with difficult and dangerous working situations. One of the efforts to protect workers in Occupational Safety and Health (OSH) is by supplying Personal Protective Equipment (PPE). This study analyzes the correlation between knowledge and compliance with personal protective equipment (PPE) used in construction workers. This paper correlated quantitative research with a cross-sectional approach. The study population was all construction workers at EMC Alam Sutera Hospital, South Tangerang, totaling 70 people. There were 70 respondents with a total sampling technique. The instruments were PPE compliance observation sheets and PPE knowledge questionnaires. Data analysis was univariate and bivariate analysis. Results showed that most respondents were 40 or older (60%). In addition, half of them had secondary and tertiary education (54.3%). Most also had good knowledge about PPE (65.7%). Of the 46 construction workers with good PPE knowledge, 42 complied with PPE use (91.3), and only four were not compliant (8.7%). Meanwhile, of the 24 construction workers with poor knowledge of PPE, 11 were not compliant with PPE use (45.8%), and 13 were compliant (54.3%). The statistical test results obtained were p=0.001. Thus, there was a significant correlation between knowledge and compliance with PPE use in respondents. In conclusion, knowledge correlates compliance with PPE uses among construction workers in EMC Alam Sutera Hospital, South Tangerang City. The hospital should provide recommendations to construction companies at EMC Alam Sutera Hospital, South Tangerang City, regarding using full PPE for construction workers.